Age-Related Changes in Skeletal Muscle of Cattle. (March 2016) - Costagliola, A.; Wojcik, S.; Pagano, T. B.; De Biase, D.; Russo, V.; Iovane, V.; Grieco, E.; Papparella, S.; Paciello, O.
Sarcopenia, the age-related loss of muscle mass and strength, is a multifactorial condition that represents a major healthcare concern for the elderly population. Although its morphologic features have been extensively studied in humans, animal models, and domestic and wild animals, only a few reports about spontaneous sarcopenia exist in other long-lived animals. In this work, muscle samples from 60 healthy Podolica-breed old cows (aged 15–23 years) were examined and compared with muscle samples from 10 young cows (3–6 years old). Frozen sections were studied through standard histologic and histoenzymatic procedures, as well as by immunohistochemistry, immunofluorescence, and Western blot analysis. The most prominent age-related myopathic features seen in the studied material included angular fiber atrophy (90% of cases), mitochondrial alterations (ragged red fibers, 70%; COX-negative fibers, 60%), presence of vacuolated fibers (75%), lymphocytic (predominantly CD8+) inflammation (40%), and type II selective fiber atrophy (40%). Immunohistochemistry revealed increased expression of major histocompatibility complex I in 36 cases (60%) and sarcoplasmic accumulations of β-amyloid precursor protein–positive material in 18 cases (30%). In aged cows, muscle atrophy was associated with accumulation of myostatin. Western blot analysis indicated increased amount of both proteins—myostatin and β-amyloid precursor protein—in muscles of aged animals compared with controls. These findings confirm the presence of age-related morphologic changes in cows similar to human sarcopenia and underline the possible role of amyloid deposition and subsequent inflammation in muscle senescence.